Altered mitochondrial epigenetics associated with subchronic doxorubicin cardiotoxicity - Ferreira, André (2017)
Doxorubicin (DOX), a potent and broad-spectrum antineoplastic agent, causes an irreversible, cumulative and dose-dependent cardiomyopathy that ultimately leads to congestive heart failure. The mechanisms responsible for DOX cardiotoxicity remain poorly understood, but seem to involve mitochondrial dysfunction on several levels. Epigenetics may explain a portion of this effect. Since mitochondrial dysfunction may affect the epigenetic landscape, we hypothesize that this cardiac toxicity may result from epigenetic changes related to disruption of mitochondrial function. To test this hypothesis, eight-week-old male Wistar rats (n=6/group) were administered 7 weekly injections with DOX (2mgkg-1) or saline, and sacrificed two weeks after the last injection. We assessed gene expression patterns by qPCR, global DNA methylation by ELISA, and proteome lysine acetylation status by Western blot in cardiac tissue from saline and DOX-treated rats. We show for the first time that DOX treatment decreases global DNA methylation in heart but not in liver. These differences were accompanied by alterations in mRNA expression of multiple functional gene groups. DOX disrupted cardiac mitochondrial biogenesis, as demonstrated by decreased mtDNA levels and altered transcript levels for multiple mitochondrial genes encoded by both nuclear and mitochondrial genomes. Transcription of genes involved in lipid metabolism and epigenetic modulation were also affected. Western blotting analyses indicated a differential protein acetylation pattern in cardiac mitochondrial fractions of DOX-treated rats compared to controls. Additionally, DOX treatment increased the activity of histone deacetylases. These results suggest an interplay between mitochondrial dysfunction and epigenetic alterations, which may be a primary determinant of DOX-induced cardiotoxicity.